Living with Ulcerative Colitis in Japan: Biologic Persistence and Health-Care Resource Use - Danielle Bargo (Karger Publishers, 2021)
Objective: The aim of the study was to improve understanding of adherence and persistence to biologics, and their association with health-care resource utilization (HCRU), in Japanese patients with moderate to severe ulcerative colitis (UC). Methods: Data were from Medical Data Vision, a secondary care administrative database. A retrospective, longitudinal cohort analysis was conducted of data from UC patients initiating biologic therapy between August 2013 and July 2016. Data collected for 2 years prior (baseline) and 2 years after (follow-up) the index date were evaluated. Patients completing biologic induction were identified, and adherence/persistence to biologic therapy calculated. HCRU, steroid, and immunosuppressant use during baseline and follow-up were assessed. Biologic switching during the follow-up was evaluated. Descriptive statistics (e.g., means and proportions) were obtained and inferential analyses (from Student’s t tests, Fisher’s exact tests, χ2 tests, the Cox proportional hazard model, and negative binomial regression) were performed. Results: The analysis included 649 patients (adalimumab: 265; infliximab: 384). Biologic induction was completed by 80% of patients. Adherence to adalimumab was higher than that to infliximab (p < 0.001). Persistence at 6, 12, 18, and 24 months was higher with infliximab than with adalimumab (p < 0.05). Overall, gastroenterology outpatient visits increased, and hospitalization frequency and duration decreased, from baseline to follow-up. UC-related hospitalizations were fewer and shorter, and endoscopies fewer, in persistent than in nonpersistent patients, although persistent patients made more outpatient visits than nonpersistent patients. Hospitalization duration was lower in persistent than nonpersistent patients. Approximately 50% of patients received an immunosuppressant during biologic therapy; 5% received a concomitant steroid during biologic therapy. Overall, 17% and 3% of patients, respectively, received 2nd line and 3rd line biologics. Conclusions: Poor biologic persistence was associated with increased non-medication-associated HCRU. Effective treatments with high persistence levels and limited associated HCRU are needed in UC.